2022
DOI: 10.2196/32212
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Versus Print-Based Physical Activity Intervention for Community-Dwelling Older Adults: Crossover Randomized Trial

Abstract: Background Fewer than half of older German adults engage in the recommended levels of endurance training. Objective The study aim is to compare the acceptance and effectiveness of two interventions for physical activity (PA) promotion among initially inactive community-dwelling older adults ≥60 years in a 9-month, crossover randomized trial. Methods Participants were recruited in person and randomized to one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Ten studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] referred to published protocols [ 79 , 80 , 81 , 82 , 83 , 84 ] or trial registry records (trial IDs reported in Table 1 ) which were consulted in these cases. Nine studies [ 69 , 70 , 73 , 76 , 77 , 78 , 85 , 86 , 87 ] were judged to be of high risk of bias and four studies [ 71 , 72 , 74 , 75 ] to have some concerns. No studies were judged to be of low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] referred to published protocols [ 79 , 80 , 81 , 82 , 83 , 84 ] or trial registry records (trial IDs reported in Table 1 ) which were consulted in these cases. Nine studies [ 69 , 70 , 73 , 76 , 77 , 78 , 85 , 86 , 87 ] were judged to be of high risk of bias and four studies [ 71 , 72 , 74 , 75 ] to have some concerns. No studies were judged to be of low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In two instances [ 88 , 89 ], the authors referred to an additional paper containing more detailed information on the respective study [ 90 , 91 ]. Of the 15 included studies, 14 studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] were published in peer-reviewed journals, 14 were written in English [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] and one [ 86 ] in German. The country of origin was Germany for 13 studies [ 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 86 , 87 , 88 ] and Belgium [ 89 ] and the UK [ 72 ] for one study each.…”
Section: Resultsmentioning
confidence: 99%
“…This has also been reported by other authors [ 79 ]. As a reaction, the study design for PROMOTE 2 was adapted such that participants could change the type of materials provided at a defined time point on a preference basis, which could improve the loss of participants because of this aspect, as well as the satisfaction with the intervention in a recognizable way [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the results of the first study indicated that predominantly already active individuals participated in the study, the exclusion criteria for PROMOTE 2 were modified, and individuals were excluded if they reported being regularly physically active for at least 2.5 hours per week for >1 year before the start of the study. Potential study participants for PROMOTE 2 were excluded if they had already participated in PROMOTE 1 [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation